Ceftriaxone sodium degradation by carbon quantum dots (CQDs)-decorated C-doped α-Bi2O3 nanorods - Xianbo Sun; Ying Pan; Yanyu Song; Liu, Wen; Long D. Nghiem; Qilin Wang; Cai, Zhengqing (Environmental Science and Ecotechnology, 2023)
A novel carbon quantum dots decorated C-doped α-Bi2O3 photocatalyst (CBO/CQDs) was synthesized by solvothermal method. The synergistic effect of adsorption and photocatalysis highly improved contaminants removal efficiencies. The ceftriaxone sodium degradation rate constant (k) of CBO/CQDs was 11.4 and 3.2 times that of pure α-Bi2O3 and C-doped α-Bi2O3, respectively. The interstitial carbon doping generated localized states above the valence band, which enhanced the utilization of visible light and facilitated the separation of photogenerated electrons and holes; the loading of CQDs improved the charge carrier separation and extended the visible light response; the reduced particle size of CBO/CQDs accelerated the migration of photogenerated carriers. The •O2− and h+ were identified as the dominant reactive species in ceftriaxone sodium degradation, and the key role of •O2− was further investigated by NBT transformation experiments. The Fukui index was applied to ascertain the molecular bonds of ceftriaxone sodium susceptible to radical attack, and intermediates analysis was conducted to explore the possible degradation pathways. The toxicity evaluation revealed that some degradation intermediates possessed high toxicity, thus the contaminants require sufficient mineralization to ensure safe discharge. The present study makes new insights into synchronous carbon dopping and CQDs decoration on modification of α-Bi2O3, which provides references for future studies.
Keywords: Antibiotics; C-doped; Carbon quantum dots; Photocatalytic; Toxicity assessment